The influence of ukhuwwah in the dynamic interplay of technological change and competitive advantage for business sustainability: the case of small and medium enterprises (SMEs) in Malaysia - Gerinsa, Muhammad Mikhail; Mhd. Sarif, Suhaimi (Zes Rokman Resources, 2019)
Technological change is continuous in the dynamic business world. In the competitive world, companies are struggling to create, maintain and sustain competitive advantage for superior performance and survival in the business. While survival for profitability and growth is essential, business continuity for sustainability is paramount. This is more challenging among small and medium enterprises when they are more vulnerable to the dynamic changes in the market. Nevertheless, the similar nature of SMEs in terms of size, nature and tenure, allows them to have more cohesiveness, or ukhuwwah in the Tawhidic paradigm. Ukhuwwah is long tenured relationship among members to attain for common goals. This study aims to explore the influence of ukhuwwah in the dynamic interplay of technological change and competitive advantage for business sustainability among SMEs in Malaysia. This study is very significant in terms of its contribution to the theory and practice from contingency perspectives, which is based on soul, spirituality and consciousness. The study used personal interview with managers of SMEs to solicit their views pertaining to the influence of ukhuwwah in sustaining their businesses. The informants argued that technological change helps to create competitive advantage for them through strategic alliances and smart partnership among the SMEs that facilitated by financing agencies and sponsors of ventures. The future study should use case study method to include more perspectives from key stakeholders.